Coulson and Richardson s Chemical Engineering: Vol.2: Particle Technology and Separation Processes - Richardson (J F); Harker (J H); Backhurst (J R) ("17-A / 1, Main Ring RoadLajpat Nagar IV,New Delhi,New Delhi,India-110 024", 2006)
Chemical Engineering
22.5
Keywords: Chemical Engineering